2021
DOI: 10.1111/jgs.17420
|View full text |Cite
|
Sign up to set email alerts
|

Pain treatment and functional improvement in home health care: Relationship with dementia

Abstract: Background Pain management is important to post‐acute functional recovery, yet older persons with Alzheimer's disease and related dementias (ADRD) are often undertreated for pain. The main objectives were (1) to examine the relationship between ADRD and analgesic use among Medicare home health care (HHC) recipients with daily interfering pain, and (2) to examine the impact of analgesic use on functional outcome in patients with and without ADRD. Methods We analyzed longitudinal data from the Outcome and Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…These symptoms raise questions about clinical management of ADRD and/or cognitive impairment in the HHC setting. Indeed, previous work 20,36 has suggested that pain is inadequately managed for HHC patients with ADRD; without access to data from OASIS care plans, we are unable to shed light on care processes associated with these symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…These symptoms raise questions about clinical management of ADRD and/or cognitive impairment in the HHC setting. Indeed, previous work 20,36 has suggested that pain is inadequately managed for HHC patients with ADRD; without access to data from OASIS care plans, we are unable to shed light on care processes associated with these symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…Serving over 3.3 million Medicare beneficiaries every year, 34,35 HHC is a leading provider of home-based care for older adults, 36 including home medication review and reconciliation, 19,37 making them an invaluable source for identifying antipsychotic use. Moreover, HHC clinicians should play a bigger role in deprescribing antipsychotics as they can help meet the underlying needs that cause BPSD, 14 such as by assessing and managing pain, 38,39 monitoring symptom changes in medical conditions, 40 removing stressors in the home (e.g., noise, temperature, light), and educating the patients and caregivers, as well as providing social contact. For patients living with ADRD who experience BPSD, better access to behavioral interventions should be provided that includes insurance coverage, prescriber awareness, and patient and caregiver access to dementia care and support resources.…”
Section: Discussionmentioning
confidence: 99%
“…According to Beers criteria, those with chronic kidney and liver failure should avoid non-steroidal anti-inflammatory drugs (NSAIDs), [28] narrowing the options for pharmacological pain medication in this population. Some alternative pain medications include acetaminophen, lidocaine patches, and selective norepinephrine reuptake inhibitors (SNRIs) [28] Non-opioids should be considered first-line therapeutics, and include aspirin and acetaminophen, gabapentin, and SNRIs [12] Gabapentin/ pregabalin, lamotrigine, or SNRIs should be used in neuropathic pain instead of tricyclic antidepressants (TCAs) due to their cardiovascular contraindications [29].…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Nurses play the most important roles in pain identification, assessment and management in CIOAs as they are at the patient's bedside providing direct care, often spending the most time with the patient, building rapport, and gaining invaluable information regarding the patient's condition and behaviors. However, recent survey studies reported nurses caring for CIOAs having fears, lack of confidence and experience, and limited knowledge of dementia care [7,8] These factors have been linked to the delay of pain identification and assessment, underuse of pro re nata (PRN) pain medication, and suboptimal treatment compared to their cognitively intact counterparts [4,7,9,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%